The Relevance of Fazlurrahman's Thoughts to Islamic Education in the Modern Era - Nur Jannah; Syamsul Aripin (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the relevance of Fazlurrahman's thoughts to Islamic education in the modern era. Fazlurrahman, a 20th-century Muslim thinker, is known for his innovative methodological approach to understanding and interpreting Islamic teachings. In the context of education, his thoughts offer important insights into how Islamic education can evolve in line with the challenges of the modern era. This study aims to examine the implementation of character education in the Implementation of Moral Education in Integrated Elementary School 01 Ujung Harapan Bahagia, Babelan, Bekasi. The study uses a qualitative approach. The research subjects are group teachers, students. Data collection techniques use interviews, observations, and documentation. Data validity is obtained through technical triangulation, source triangulation and reference adequacy. Data are analyzed using Miles & Huberman analysis techniques, namely data collection, data reduction, data presentation, and decision making. The results of the study show that; (1) Morning Recitation can be used as a Character Education Approach (2 Teacher's exemplary behavior can be used as a Character Education Model (3) Moral Story-Based Learning from the Qur'an and Hadith can be influential as Character Education.